Recommendations from primary care providers for integrating mental health in a primary care system in rural Nepal - Acharya, Bibhav (BMC Health Serv Res, 2016)
BACKGROUND: Globally, access to mental healthcare is often lacking in rural, low-resource settings. Mental healthcare services integration in primary care settings is a key intervention to address this gap. A common strategy includes embedding mental healthcare workers on-site, and receiving consultation from an off-site psychiatrist. Primary care provider perspectives are important for successful program implementation. METHODS: We conducted three focus groups with all 24 primary care providers at a district-level hospital in rural Nepal. We asked participants about their concerns and recommendations for an integrated mental healthcare delivery program. They were also asked about current practices in seeking referral for patients with mental illness. We collected data using structured notes and analyzed the data by template coding to develop themes around concerns and recommendations for an integrated program. RESULTS: Participants noted that the current referral system included sending patients to the nearest psychiatrist who is 14 h away. Participants did not think this was effective, and stated that integrating mental health into the existing primary care setting would be ideal. Their major concerns about a proposed program included workplace hierarchies between mental healthcare workers and other clinicians, impact of staff turnover on patients, reliability of an off-site consultant psychiatrist, and ability of on-site primary care providers to screen patients and follow recommendations from an off-site psychiatrist. Their suggestions included training a few existing primary care providers as dedicated mental healthcare workers, recruiting both senior and junior mental healthcare workers to ensure retention, recruiting academic psychiatrists for reliability, and training all primary care providers to appropriately screen for mental illness and follow recommendations from the psychiatrist. CONCLUSIONS: Primary care providers in rural Nepal reported the failure of the current system of referral, which includes sending patients to a distant city. They welcomed integrating mental healthcare into the primary care system, and reported several concerns and recommendations to increase the likelihood of successful implementation of such a program. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12913-016-1768-9) contains supplementary material, which is available to authorized users.